Format Checks and Balances Badan Pemeriksa Keuangan dan Dewan Perwakilan Rakyat Pasca Penguatan Fungsi Pengawasan Dewan Perwakilan Rakyat: Format of Checks and Balances Between The Audit Board and The House of Representatives Following The Strengthening of The Supervisory Function of The House of Representatives - Roziqin (SHARE Journal, 2025)
The relationship between the House of Representatives DPR and other state institutions operates on a system of checks and balances to prevent abuse of power. This study analyzes the checks and balances structure between the Audit Board BPK and the DPR following the strengthening of the DPR's supervisory function in 2025, as set forth in an Amendment to the DPR's Rules of Procedure. Employing a normative legal method and statute approach, this study analyzes the hierarchy of regulations and the division of powers. Prior to the Amendment, checks and balances between the DPR and the BPK primarily involved the DPR selecting BPK members, offering advice on audit planning, and inquiry into audit results. The Amendment enhances DPR's capacity by empowering it to evaluate BPK members, thereby strengthening supervisory functions. Nonetheless, this change does not alter the fundamental checks and balances, as both DPR Regulations and Presidential Regulations are equal based on the legal hierarchy. Furthermore, both the BPK and DPR also have parallel authority, thereby confirming that the Amendment to the DPR’s Rules of Procedure serve only to strengthen the DPR's supervisory function without changing the established checks and balances between the BPK and DPR, as set out in existing laws and regulations.